The interaction patterns and the development of the productive english skills with the students of 7th, 8th, 9th and 10th years of basic education at educative unit “Miguel Riofrío’’ No1 of Loja city. Academic period 2013-2014 - Balcázar Cueva, Tania Marixa (2016)
The research work “THE INTERACTION PATTERNS AND THE DEVELOPMENT OF THE PRODUCTIVE ENGLISH SKILLS WITH THE STUDENTS OF 7 th, 8th, 9th AND 10th YEARS OF BASIC EDUCATION AT EDUCATIVE UNIT “MIGUEL RIOFRÍO‟ NO1 OF LOJA CITY. ACADEMIC PERIOD 2013-2014”, was developed in order to determine the contribution of the interaction patterns in the development of productive English skills. The methods implemented to develop the research were: descriptive, explanatory and analytic- synthetic. In addition, surveys were applied to teachers and students, which were used as instruments to collect data. Then, it was tabulated, organized and described in the statistical tables, graphically represented, interpreted and analyzed in a logical process that allowed determining conclusions and making recommendations. The results of the research, it was concluded that interaction patterns are useful in developing the productive skills, and teachers are applying these patterns that reflect the students improve the productive skills